Improving the Academic English Achievement through Developing Students’ Self-Efficacy of Verbal Persuasions; A Classroom Action Research - Situmorang, Komilie (Journal of Languages and Language Teaching, 2022)
Self-efficacy is a drive within students that affects their thinking, feeling, motivation, and learning activities to achieve what they need. It is said to be one of the predictors of academic success leading to its urgency put into research.   The study is classroom action research aiming to improve the nursing students' scores in Academic English class by raising the students’ self-efficacy through giving verbal persuasions. This action research was designed following Kemmis and McTaggarts’ model, including Planning, Action, Observation, and Reflection. 42 participants were also active students in the class of Academic English. After completing the sessions, the students were given pre-and posttest and asked to reflect on their achievements. The findings indicate that the average scores increased by 25 points between pre-and-posttest, 83.33% of participants had increased self-confidence, and 90.47% were satisfied with their test results. Further, the study shows score improvement through review, restudy, and re-try, pointing out the emergence of self-efficacy, which is not instant. It is a result of consistency and belief through the verbal persuasion given by the teacher.